Effectiveness of Hydrated Sodium Calcium Aluminosilicate (HSCAS) in Mitigating the Adverse Effects of Aflatoxin on In Vitro Rumen Fermentation of Wheat Straw - Singh, Ram; Saini, Ashwani Kumar; Dhial, Kritika; Pathak, Abhishek (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
To study the effect of hydrated sodium calcium aluminosilicate (HSCAS) in ameliorating adverse effects of aflatoxin on in vitro rumen fermentation, five treatment groups, viz., T1: control (wheat straw; 0.2 g); T2: T1+300 ppb Aflatoxin B1 (AFB1); T3: T2+0.33% HSCAS; T4: T2+0.5% HSCAS and T5: T2+ 1.0% HSCAS were prepared and incubated in vitro. The results revealed that truly degradable dry matter (TDDM), truly degradable organic matter (TDOM), gas production (GP), microbial biomass production (MBP) and partitioning factor (PF) values in aflatoxin contaminated group (T2) were lower (p<0.05) than those of other treatment groups. The TDDM, TDOM, GP, MBP and PF values in control group (T1) were higher than those of other treatment groups, i.e., T2 to T5. These parameters improved with increasing concentration of HSCAS. The total volatile fatty acids (TVFA), acetate (A), propionate (P) and butyrate (B) values in control group (T1) were higher (p<0.05) than those of other treatment groups, i.e., T2 to T5. The TVFA, A, P and B values in aflatoxin contaminated T2 group were lower (p<0.05) than those of other treatment groups. The A:P value among various dietary treatments did not vary significantly. It was concluded that aflatoxin contamination of feed (wheat straw) at 300 ppb level significantly affected the in vitro rumen fermentation in terms of reduced TDDM, TDOM, GP, MBP, PF, TVFA concentration. Inclusion of hydrated sodium calcium aluminosilicate to the aflatoxin contaminated feed partially ameliorated the adverse effects of aflatoxin on in vitro rumen fermentation parameters.